2013
DOI: 10.1017/s1479262113000282
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic characterization of indigenous rice (Oryza sativa L.) germplasm collected from the state of Nagaland, India

Abstract: Nagaland is one of the eight states in the north-eastern region of India, where a considerable diversity exists in cultivated rice. Recent exploration in this tribal-dominated state has resulted in a collection of 130 rice accessions growing under diverse agroecological conditions. The agromorphological characterization data of 124 rice landraces revealed a significant variability in plant architecture and grain morphological and quality traits. Multivariate analyses including principal component analysis (PCA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 17 publications
3
10
0
Order By: Relevance
“…The grouping of hill rice accessions in both PCA and Ward’s cluster did not follow geographical origin for a genotype. Similar trend was also recorded in previous studies [ 47 , 49 ]. The average number of panicles per plant in hill rice accessions of Arunachal Pradesh (5.30) is lower than those reported in rice landraces from Nagaland state (7.9) [ 47 ] and rice cultivars adapted to high-altitude environments in Nepal (8.0) [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The grouping of hill rice accessions in both PCA and Ward’s cluster did not follow geographical origin for a genotype. Similar trend was also recorded in previous studies [ 47 , 49 ]. The average number of panicles per plant in hill rice accessions of Arunachal Pradesh (5.30) is lower than those reported in rice landraces from Nagaland state (7.9) [ 47 ] and rice cultivars adapted to high-altitude environments in Nepal (8.0) [ 48 ].…”
Section: Discussionsupporting
confidence: 92%
“…Similar trend was also recorded in previous studies [ 47 , 49 ]. The average number of panicles per plant in hill rice accessions of Arunachal Pradesh (5.30) is lower than those reported in rice landraces from Nagaland state (7.9) [ 47 ] and rice cultivars adapted to high-altitude environments in Nepal (8.0) [ 48 ]. Extremely strong selection pressure for adaptation to the harsh high-altitude environments and direct seeding method of planting could have limited the number of productive tillers in hill rice germplasm.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Local varieties are valuable as they possess a huge treasure of genetic material for development and improvement programs. Several researchers reported the use of agromorphological markers in the characterization and study of rice (Oryza sativa L.) germplasm diversity in China (Yawen et al, 2003), India (Roy et al, 2013), Vietnam (Nguyen et al, 2009), Nepal (Mahendra et al, 2013) and even in Africa (Semon et al, 2005;Barry et al, 2007;Nuijten et al, 2009;Sow et al, 2013). In Benin and in our knowledge, no genetic diversity study on rice is reported.…”
Section: Introductionmentioning
confidence: 99%
“…The Eastern Himalayan region of Northeast (NE) India, which spans over 255,000 km 2 covering Arunachal Pradesh, Assam, Manipur, Meghalaya, Mizoram, Nagaland and Tripura states (Figure 1 ) is home to a large number of indigenous rice varieties [ 1 3 ]. Such varieties are cultivated under diverse agro-climatic conditions and distributed over a broad geographical area ranging from flood plains and lower catchment areas of the Brahmaputra and Barak rivers to high altitude mountains of the Himalayas.…”
Section: Introductionmentioning
confidence: 99%